Challenges Faced by Teachers and Students in Teaching-Learning Reaction Mechanism - Pratap, Narendra; Devkota, Krishna Maya (Education Quarterly, 2024)
This study explores teachers’ and students’ difficulties while teaching and learning chemical reaction mechanisms. It included a sample of forty students and four teachers. It was carried out across two of the constituent campuses of TU. Likert scale statements were used in the quantitative methodology employed for the study to measure the difficulties teaching and learning reaction mechanisms. In-depth interviews and Focus Group Discussions (FGDs) with ten students and two purposefully chosen teachers also provided qualitative insights. The results show that students have difficulty in learning inductance, polar covalent bonds, SN1 and SN2 reactions, and homolytic and heterolytic bond fission. Similarly, educators face difficulties restricting pupils’ insufficient basic comprehension in modulation and visualization. The use of 3D simulation and modulation can improve understanding of reaction processes. The highlighted areas of this study need intervention to enhance teaching and learning of chemical reaction mechanisms.